Constituição cidadã e representações sociais: uma reflexão sobre modelos de assistência à saúde - SILVA, Sílvio Éder Dias da (2014)
This article presents a reflection on the meaning of the terms citizenship and health, addressing the Theory of Social Representations as a strategy for implementing and evaluating health care models in Brazil. First, a brief history about the concept of citizenship is presented; then the article addresses the principles of freedom and equality according to Kant; the third section of the article shows that health is as a right of the citizen and a duty of the state. Finally, the Theory of Social Representations is emphasized as a strategy to evaluate and implement the health services provided to citizens by the current health care models in Brazil.